Citizens’ Satisfaction With Local Government Service Delivery Performance in Bangladesh: Does Citizens’ Confidence Matter? - Islam, Md Shahriar; Ahsan, Abu Hossain Muhammad (Social Science Review, 2023)
The purpose of this study is to explain the relationship between perceived quality of local service delivery performance and citizens’ satisfaction through confidence at urban local government level in Bangladesh. A mediation model was framed to test the indirect relationship between perceived quality of service delivery performance and citizens’ satisfaction. Data was collected through a survey during April 2014 – June 2014. The survey included ten Paurashavas (Municipality) while the participants (n = 706) were selected based on gender ratio and Ward of the Paurashavas. Multilevel path analysis was conducted using MPLUS 8 to examine the mediation model. The results showed that citizens’ confidence partially mediates the relationship between perceived quality of service delivery performance and citizens’ satisfaction. Social Science Review, Vol. 38(2), December 2021 Page 117-133